Research in technology and second language education developments and directions - Zhao, Yong, 1965- (Emerald Publishing Limited : IAP-Information Age Publishing, 2005)
Zhao (Michigan State U.) presents a collection of 17 articles reporting on empirical studies on the effective use of computer-assisted language learning (CALL). Written by 27 academics and researchers, all but one from the U.S., the majority of the articles were previously published in scholarly journals and books.
Keywords: Language and languages -- Study and teaching -- Technological innovations.; Educational technology.; Language Arts & Disciplines -- Study & Teaching.; Language teaching and learning material and coursework.; Language teaching and learning.; elektronické knihy; electronic books